Preparation method of phase change heat storage catalyst

By adopting the Al@Al2O3@SiO2 phase change thermal storage catalyst with a bishell core-shell structure, the problem of isolation between the heat storage body and the catalyst in traditional thermal storage catalytic combustion is solved, the coupling of catalytic and thermal storage functions is achieved, and the combustion efficiency of low-concentration methane and the service life of the catalyst are improved.

CN119771399APending Publication Date: 2025-04-08KUNMING UNIV OF SCI & TECH +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411965110.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the conventional catalytic combustion of the thermal storage body and the catalyst are isolated from the thermal storage body, resulting in low thermal management efficiency and it is difficult to achieve effective combustion of low concentration methane.

Method used

The Al@Al2O3@SiO2 phase change heat storage catalyst adopts a bishell core-shell structure, and the thermal control of methane catalytic combustion is achieved by constructing the Al2O3 and SiO2 shells wrapped in metal Al cores, and the absorption/exothermic heat during the phase change is used.

Benefits of technology

The coupling of catalytic and heat storage functions is achieved, the volume of traditional heat storage combustion devices is reduced, and the heat storage capacity of the material and the service life of the catalyst are improved, and the combustion efficiency of low-concentration methane is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771399A_ABST
    Figure CN119771399A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a phase change heat storage catalyst. The preparation method specifically comprises the following steps: (1) roasting aluminum powder, and ultrasonically dispersing the aluminum powder in water; (2) adding hexadecyl trimethyl ammonium bromide, stirring, adding a monohydric alcohol solvent, and continuously stirring; (3) adding ammonia water, adding tetraethoxysilane, sealing, reacting, standing, carrying out solid-liquid separation, washing, drying and roasting; and (4) dispersing in a precursor solution of noble metal, stirring, drying and roasting to obtain the catalyst. The precious metal is loaded on the Al (at) Al2O3 (at) SiO2 phase change heat storage material with the double-shell core-shell structure, the catalysis function and the heat storage function are coupled, heat storage and catalysis are integrated, the size of a traditional heat storage combustion device is greatly reduced, and meanwhile the heat storage capacity of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermal storage catalysis, and more particularly to a method for preparing a phase-change thermal storage catalyst. Background Art

[0002] Coalbed methane (commonly known as gas) is an unconventional natural gas with methane as the main component and adsorbed in coal seams. It is not only an important greenhouse gas, but also a clean energy with abundant reserves. Its development and utilization have attracted the attention of governments and researchers around the world. For safety reasons, the volume concentration of methane emitted by industry is usually diluted to less than 5% (lower explosion limit). Under the conditions of low methane concentration (0.1%-1%), large flux and high impurity content, most mine ventilation air is difficult to develop and utilize using conventional technology. It is directly discharged into the atmosphere without recycling and treatment according to the mining situation. The flammable range of methane in conventional combustion technology is 5%-15%. Unless the ambient temperature exceeds 1000℃, methane cannot be ignited or continuously burned at less than 5%. However, due to the low methane concentration, the reaction heat is difficult to maintain such a high temperature.

[0003] At present, the development of low-concentration methane combustion catalysts and reactors has become a research hotspot. There are two main solutions for the comprehensive utilization of low-concentration methane as the main fuel: on the one hand, the development of new catalysts can significantly reduce the reaction temperature; on the other hand, improving the combustion process and optimizing the reactor design so that the reactor can maintain self-heating operation at high temperatures to meet the combustion conditions of low-concentration methane. As an efficient and environmentally friendly oxidation technology, catalytic combustion can remove low-concentration methane as the main fuel and replace traditional thermal combustion to provide a certain amount of heat.

[0004] Thermal energy management is very important for heterogeneous reactions that need to absorb or release a large amount of heat. Thermal storage system is one of the most important branches of thermal energy management because it can significantly improve energy utilization efficiency and make up for the mismatch between energy supply and demand. Phase change materials can store or release heat through a continuous phase change process, and have a high heat storage density and an appropriate phase change temperature range, which makes the system smaller and more efficient, so phase change materials are considered to be ideal thermal storage materials. Microcapsule phase change thermal storage materials have excellent heat storage capacity, high melting rate and good structural stability, which makes them a promising material for thermal management in many chemical processes, such as catalytic oxidation of fuels. For unstable heat sources, the high heat storage density of microcapsule phase change thermal storage materials can reduce the difficulty of controlling temperature fluctuations and improve system efficiency. Constructing thermal storage catalysts and using the rapid melting of phase change materials at a certain temperature can effectively avoid thermal runaway and optimize the temperature distribution of the catalyst bed in exothermic reactions. For non-steady-state chemical processes, in-situ storage of heat in the catalyst will enhance the heat exchange between the exothermic and endothermic parts.

[0005] Therefore, how to develop a heat storage catalyst is an urgent problem to be solved by those skilled in the art. Summary of the invention

[0006] In view of this, the object of the present invention is to provide a method for preparing a phase change thermal storage catalyst to solve the problems of isolation between the thermal storage body and the catalyst in the conventional thermal storage catalytic combustion in the prior art.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] A method for preparing a phase-change thermal storage catalyst comprises the following steps:

[0009] (1) Firstly, aluminum powder is calcined, and then ultrasonically dispersed in water to obtain an aluminum powder suspension;

[0010] (2) firstly adding hexadecyltrimethylammonium bromide to the aluminum powder suspension, stirring, then adding a monohydric alcohol solvent, continuing to stir, to obtain a mixed solution;

[0011] (3) first adding ammonia water to the mixed solution, then adding tetraethyl orthosilicate, sealing, reacting, standing, solid-liquid separation, washing, drying, and roasting to obtain Al@Al2O3@SiO2 phase change thermal storage material;

[0012] (4) Ultrasonic dispersion of Al@Al2O3@SiO2 phase change thermal storage material in a precursor solution of a precious metal, stirring, drying, and calcining to obtain an Al@Al2O3@SiO2 phase change thermal storage catalyst.

[0013] The preparation process of the present invention is as follows: aluminum powder is first subjected to thermal oxidation treatment to form an Al2O3 film with a certain thickness, and then SiO2 is wrapped onto the aluminum powder after the thermal oxidation treatment by controlling the hydrolysis time of ethyl orthosilicate under alkaline conditions in an alcohol-water system, and calcination in air can form a stable and dense oxide shell layer on the surface of the powder, and then noble metal impregnation is performed to finally form a double-shell core-shell structure Al@Al2O3@SiO2 phase change thermal storage catalyst loaded with noble metals.

[0014] The reaction mechanism of the invention is: spherical oxide or hydroxide particles are prepared by hydrolysis of alcohol salts. In the presence of only water and alcohol solvent, the hydrolysis rate of silicon alcohol salt (ethyl orthosilicate) is slow, so it is necessary to add ammonia water as a catalyst to prepare SiO2 microspheres. The addition of hexadecyltrimethylammonium bromide can adjust the porosity and increase the specific surface area. By adjusting the amount of hexadecyltrimethylammonium bromide, monohydric alcohol, water, ammonia water and ethyl orthosilicate and the reaction time, SiO2 silicon can be effectively and evenly wrapped on the surface of aluminum powder after thermal oxidation treatment.

[0015] The heat storage catalytic principle of the present invention is: by constructing a double shell of Al2O3 and SiO2 to protect the metal Al inner core, the heat absorption / release during phase change is utilized to achieve heat control of the methane catalytic combustion heat release process. During the heat storage process, the heat storage inner core metal Al absorbs the heat released by combustion to undergo solid-liquid phase transition, achieving the effect of heat storage-temperature control; when the external temperature drops, the heat storage inner core metal Al releases the stored heat and undergoes liquid-solid transition, providing stable operation of the precious metal catalyst while slowing down the temperature drop of the hot bed. In this process, the oxidation shell has high strength and density, which can prevent the leakage of liquid alloy.

[0016] The beneficial effects of the present invention are: loading precious metals onto the double-shell core-shell structure Al@Al2O3@SiO2 phase-change thermal storage material, coupling the catalytic and thermal storage functions, and realizing the integration of thermal storage and catalysis, which will greatly reduce the size of traditional thermal storage combustion devices, while improving the heat storage capacity of the material itself. The double-shell core-shell structure Al@Al2O3@SiO2 phase-change thermal storage catalyst loaded with precious metals of the present invention can achieve the regulation of the catalyst bed temperature while ensuring reliable methane catalytic combustion stability, and maintain a high thermal storage density, thereby achieving efficient energy utilization. At the same time, regulating the appropriate thickness of the double shell can take into account the thermal conductivity of the thermal storage catalyst and the anchoring point for the catalyst to land, which will be of great significance for the development of thermal storage catalytic combustion systems with high comprehensive performance in future thermal energy storage systems.

[0017] Furthermore, in the above step (1), the size of the aluminum powder is 200-1500 mesh; and the mass ratio of the aluminum powder to water is 1:(6-15).

[0018] Furthermore, in the above step (1), the calcination equipment is a muffle furnace, the heating rate is 1-20°C / min, the temperature is 500-800°C, and the time is 1-5h; the ultrasonic dispersion time is 10-30min.

[0019] Furthermore, in the above step (2), the mass ratio of aluminum powder to hexadecyltrimethylammonium bromide is 1:(0.5-2); the monohydric alcohol solvent is at least one of methanol, ethanol, n-propanol and n-butanol; and the volume ratio of water to the monohydric alcohol solvent is 1:(0.5-2.5).

[0020] Furthermore, in the above step (2), the stirring temperature is 25 to 70° C., the stirring time is 1 to 10 min, and the stirring time is continued for 5 to 20 min.

[0021] Furthermore, in the above step (3), the volume ratio of ammonia water to water is 1:(1.5-15); and the molar ratio of hexadecyltrimethylammonium bromide to tetraethyl orthosilicate is 1:(1-3).

[0022] Furthermore, in the above step (3), the conditions for adding ammonia water are 25-70° C. and stirring; the reaction time is 1-24 hours; the standing time is 0.5-1 hour; and the washing sequence is water-anhydrous ethanol-water, and the number of times is 3-5 times.

[0023] Furthermore, in the above step (3), the calcination equipment is a muffle furnace, the atmosphere is air, the temperature is 500-800° C., and the time is 0.5-4 h.

[0024] Furthermore, in the above step (4), the precious metal is Pd or Pt; the ultrasonic time is 10 to 60 minutes; and the stirring temperature is 25 to 70° C. until the water is evaporated.

[0025] Furthermore, in the above step (4), the calcination equipment is a muffle furnace, the atmosphere is air, the temperature is 500-800° C., and the time is 0.5-4 h.

[0026] It can be seen from the above technical solution that compared with the prior art, the beneficial effects of the present invention are as follows:

[0027] 1. The phase-change heat storage catalyst of the present invention has a large heat storage density. At the same time, the temperature is maintained at the phase change temperature during the phase change heat absorption / release process, which reduces the fluctuation of the reaction rate, avoids the bed temperature runaway phenomenon that occurs in industrial neutralization experiments, increases the service life of the catalyst, and reduces the economic cost; moreover, the volume of latent heat storage is smaller under the same heat storage capacity, which can save space.

[0028] 2. The phase-change heat storage catalyst of the present invention is wrapped by Al2O3 and SiO2 shells, which is resistant to high temperatures, not easy to sinter, and has enhanced mechanical strength. By selecting aluminum powder of different sizes and utilizing its microcapsule structure, the heat exchange area and the sealing of the package can be increased.

[0029] 3. The metal Al core in the phase change thermal storage catalyst of the present invention has a higher phase change enthalpy value and a higher thermal storage density compared to traditional non-metallic thermal storage materials.

[0030] 4. The present invention adopts a double-shell core-shell structure, which is beneficial to prevent the metal Al core from leaking during multiple cycles of heat absorption / release.

[0031] 5. The outer shell layer of the phase-change thermal storage catalyst of the present invention is nano-scale SiO2, which is beneficial to enhancing the specific surface area of ​​the material, while having high strength and density, and providing effective guarantee for the placement of precious metals.

[0032] 6. The raw materials of the present invention are cheap and readily available, the preparation conditions are mild, and the process flow is simple and has high controllability, and large-scale production can be achieved.

[0033] 7. The phase-change thermal storage catalyst powder of the present invention can be processed into various shapes such as spheres, flakes, and pellets. It is easy to load when used in fields such as low-concentration methane and catalytic combustion of industrial waste gas, and is suitable for different application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The scanning electron microscope (SEM) image of the phase-change thermal storage catalyst of Example 1 and its cross-sectional element scanning schematic diagram;

[0035] Figure 2 The scanning electron microscope (SEM) image of the phase-change thermal storage catalyst of Example 2 and its cross-sectional element scanning schematic diagram;

[0036] Figure 3 This is a differential scanning calorimeter (DSC) endothermic and exothermic characteristic diagram of the phase change thermal storage catalyst of Example 1;

[0037] Figure 4 This is a differential scanning calorimeter (DSC) endothermic and exothermic characteristic diagram of the phase change thermal storage catalyst of Example 2;

[0038] Figure 5 This is a diagram showing the catalytic methane combustion performance of the phase change thermal storage catalysts of Example 1 and Example 2. DETAILED DESCRIPTION

[0039] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] Example 1

[0041] The preparation method of the phase change thermal storage catalyst specifically comprises the following steps:

[0042] (1) First, 5 g of 300-mesh aluminum powder was placed in a ceramic crucible, placed in a muffle furnace, heated to 700° C. at a rate of 5° C. / min, and calcined for 3 h. Then, 75 mL of deionized water was added and ultrasonically dispersed for 10 min to obtain an aluminum powder suspension.

[0043] (2) First, add 2.74 g of hexadecyltrimethylammonium bromide to the aluminum powder suspension, stir at 25° C. for 5 min, then add 37.5 mL of methanol and continue stirring for 10 min to obtain a mixed solution;

[0044] (3) First, under stirring conditions at 25°C, 5 mL of ammonia water was added to the mixed solution, and then 5 mL of tetraethyl orthosilicate was added, the mixture was sealed, reacted for 3 h, allowed to stand for 0.5 h, solid-liquid separation was performed, and the solid was washed three times in the order of water-anhydrous ethanol-water, dried, placed in a muffle furnace, heated to 500°C in an air atmosphere, and calcined for 2 h to obtain Al@Al2O3@SiO2 phase change thermal storage material;

[0045] (4) Add Al@Al2O3@SiO2 phase change thermal storage material to the Pd precursor solution, ultrasonically disperse for 30 min, stir at 25 °C until the water evaporates, put it into a muffle furnace after drying, heat it to 500 °C in an air atmosphere and calcine it for 2 h to obtain Al@Al2O3@SiO2 phase change thermal storage catalyst.

[0046] Example 2

[0047] The preparation method of the phase change thermal storage catalyst specifically comprises the following steps:

[0048] (1) First, 5 g of 1000 mesh aluminum powder was placed in a ceramic crucible, placed in a muffle furnace and heated to 700° C. at a rate of 10° C. / min and calcined for 3 h, then added to 30 mL of deionized water and ultrasonically dispersed for 30 min to obtain an aluminum powder suspension;

[0049] (2) First, 8.23 ​​g of hexadecyltrimethylammonium bromide was added to the aluminum powder suspension, stirred at 25° C. for 10 min, and then 75 mL of ethanol was added and stirred for 20 min to obtain a mixed solution;

[0050] (3) First, under stirring conditions at 50°C, 20 mL of ammonia water was added to the mixed solution, and then 10 mL of tetraethyl orthosilicate was added, the mixture was sealed, reacted for 3 h, allowed to stand for 1 h, solid-liquid separation was performed, and the solid was washed alternately 5 times in the order of water-anhydrous ethanol-water, and after drying, it was placed in a muffle furnace, heated to 700°C in an air atmosphere, and calcined for 2 h to obtain Al@Al2O3@SiO2 phase change thermal storage material;

[0051] (4) Add Al@Al2O3@SiO2 phase change thermal storage material to the Pd precursor solution, ultrasonically disperse for 10 min, stir at 50°C until the water is evaporated, put it into a muffle furnace after drying, heat it to 500°C in an air atmosphere and calcine it for 2 h to obtain Al@Al2O3@SiO2 phase change thermal storage catalyst.

[0052] Performance Testing

[0053] 1. The scanning electron microscope image (SEM) of the Al@Al2O3@SiO2-500 phase change thermal storage catalyst prepared in Example 1 and the schematic diagram of the cross-sectional element scanning are shown in FIG. Figure 1 shown.

[0054] Depend on Figure 1 It can be seen that the micron-sized aluminum balls did not show any agglomeration phenomenon. At the same time, it can be found that a dense Al2O3 and SiO2 shell layer was formed on the outer shell of the aluminum ball, and the Si element evenly penetrated into the inner core, which is also beneficial to improve the latent heat value of the phase change heat storage catalyst.

[0055] 2. The scanning electron microscope image (SEM) of the Al@Al2O3@SiO2-700 phase change thermal storage catalyst prepared in Example 2 and the schematic diagram of the cross-sectional element scanning are shown in FIG. Figure 2 shown.

[0056] Depend on Figure 2 It can be seen that the micron-sized aluminum balls did not show any agglomeration phenomenon. At the same time, it can be found that a dense Al2O3 and SiO2 shell layer was formed on the outer shell of the aluminum ball, and the Si element also penetrated into the inner core, but there was slight agglomeration.

[0057] 3. The differential scanning calorimeter (DSC) endothermic and exothermic characteristics of the Al@Al2O3@SiO2-500 phase change thermal storage catalyst prepared in Example 1 are shown in the figure below: Figure 3 shown.

[0058] Depend on Figure 3 It can be seen that the endothermic peak is at 577°C and the main exothermic peak is at 528°C, indicating that the storage and release temperature range of the material is located near this. The melting heat (149.2J / g) and solidification heat values ​​(131.6J / g) are both very large, and the difference between the melting endothermic heat and the solidification exothermic heat is very small, indicating that the material has excellent thermal storage density and low supercooling, which is conducive to ensuring high thermal storage density and thermal conductivity efficiency. However, three cycles of heat absorption / release experiments show that the latent heat of the material decreases from 178.5J / g to 149.2J / g, indicating that when the SiO2 shell is formed under 500°C calcination conditions, its structure and heat absorption / release stability are poor.

[0059] 4. The differential scanning calorimeter (DSC) endothermic and exothermic characteristics of the Al@Al2O3@SiO2-700 phase change thermal storage catalyst prepared in Example 2 are shown in the figure below: Figure 3 shown.

[0060] Depend on Figure 3 It can be seen that the endothermic peak is at 577°C and the main exothermic peak is at 528°C, indicating that the storage and release temperature range of the material is located near this, the same as Al@Al2O3@SiO2-500. The melting heat (216.3J / g) and solidification heat values ​​(241.8J / g) are both very large, and the difference between the melting endothermic heat and the solidification exothermic heat is very small, indicating that the material also has excellent thermal storage density and low supercooling, which is conducive to ensuring high thermal storage density and thermal conductivity efficiency. In addition, three cycles of heat absorption / release experiments show that the latent heat of the material has been maintained at around 215J / g, indicating that when the SiO2 shell is formed under 700°C calcination conditions, its structure and heat absorption / release stability are good.

[0061] 5. The catalytic methane combustion performance of the Al@Al2O3@SiO2-500 phase change thermal storage catalyst prepared in Example 1 and the Al@Al2O3@SiO2-700 phase change thermal storage catalyst prepared in Example 2 is shown in the figure. Figure 4 shown.

[0062] Depend on Figure 4 It can be seen that compared with Al@Al2O3@SiO2-500, the temperature of Al@Al2O3@SiO2-700 methane catalytic combustion is nearly 100°C lower when the methane conversion rate reaches 90%. Combined with the results described above, the Al@Al2O3@SiO2-700 phase change thermal storage catalyst has better thermal storage performance and can better disperse precious metals to obtain a lower methane catalytic combustion temperature.

[0063] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a phase change thermal storage catalyst, characterized in that: The specific steps include: (1) Firstly, aluminum powder is calcined, and then ultrasonically dispersed in water to obtain an aluminum powder suspension; (2) firstly adding hexadecyltrimethylammonium bromide to the aluminum powder suspension, stirring, then adding a monohydric alcohol solvent, continuing to stir, to obtain a mixed solution; (3) first adding ammonia water to the mixed solution, then adding tetraethyl orthosilicate, sealing, reacting, standing, solid-liquid separation, washing, drying, and roasting to obtain Al@Al2O3@SiO2 phase change thermal storage material; (4) Ultrasonic dispersion of the Al@Al2O3@SiO2 phase change thermal storage material in a precursor solution of a precious metal, stirring, drying, and calcining to obtain the Al@Al2O3@SiO2 phase change thermal storage catalyst.

2. The method for preparing a phase change thermal storage catalyst according to claim 1, characterized in that: In step (1), the size of the aluminum powder is 200-1500 mesh; the mass ratio of the aluminum powder to water is 1:(6-15).

3. The method for preparing a phase change thermal storage catalyst according to claim 1, characterized in that: In step (1), the calcination equipment is a muffle furnace, the heating rate is 1-20°C / min, the temperature is 500-800°C, and the time is 1-5h; the ultrasonic dispersion time is 10-30min.

4. The method for preparing a phase change thermal storage catalyst according to claim 1, characterized in that: In step (2), the mass ratio of the aluminum powder to hexadecyltrimethylammonium bromide is 1:(0.5-2); the monohydric alcohol solvent is at least one of methanol, ethanol, n-propanol and n-butanol; and the volume ratio of water to the monohydric alcohol solvent is 1:(0.5-2.5).

5. The method for preparing a phase change thermal storage catalyst according to claim 1, characterized in that: In step (2), the stirring temperature is 25 to 70° C., and the stirring time is 1 to 10 min; and the stirring time is continued for 5 to 20 min.

6. The method for preparing a phase change thermal storage catalyst according to claim 1, characterized in that: In step (3), the volume ratio of the aqueous ammonia to water is 1:(1.5-15); the molar ratio of the hexadecyltrimethylammonium bromide to tetraethyl orthosilicate is 1:(1-3).

7. The method for preparing a phase change thermal storage catalyst according to claim 1, characterized in that: In step (3), the conditions for adding the ammonia water are 25-70° C. and stirring; the reaction time is 1-24 hours; the standing time is 0.5-1 hour; and the washing sequence is water-anhydrous ethanol-water, for 3-5 times.

8. The method for preparing a phase change thermal storage catalyst according to claim 1, characterized in that: In step (3), the calcination equipment is a muffle furnace, the atmosphere is air, the temperature is 500-800° C., and the time is 0.5-4 h.

9. The method for preparing a phase change thermal storage catalyst according to claim 1, characterized in that: In step (4), the noble metal is Pd or Pt; the ultrasonic time is 10 to 60 minutes; and the stirring temperature is 25 to 70° C. until the water is evaporated.

10. The method for preparing a phase change thermal storage catalyst according to claim 1, characterized in that: In step (4), the calcination equipment is a muffle furnace, the atmosphere is air, the temperature is 500-800° C., and the time is 0.5-4 hours.

Citation Information

Patent Citations

  • Al / Al2O3 heat storage material and preparation method thereof

    CN101798498A

  • Monolithic catalyst applied to ultralow-concentration methane combustion and preparation method thereof

    CN107899570A

  • Preparation method and application of precious metal particles / silicon dioxide wall material phase change microcapsules composite materials

    CN110240891A

  • Catalyst carrier with temperature adjustment function and preparation method of catalyst carrier

    CN110586061A

  • Preparation method of aluminum core ceramic core-shell structure composite phase change heat storage material

    CN117987088A